Islamic Self-Efficacy Training and Anxiety Facing Qur’an Memorization Tests of Tahfidz Students - Triyono, Triyono; Kholiq Hasan, Moh. Abdul; Hikmawati, Ari (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
This study aims to determine the effect of Islamic self-efficacy training to reduce anxiety in facing the Qur’an memorization test of the tahfidz students at Al-Muayyad Islamic Boarding School, Surakarta. This research is a quantitative pre-experimental design, with a one group pretest-posttest design. The sample in this study are 30 female students who were selected using purposive sampling technique. The scale used to measure the level of anxiety facing the Qur'an memorization test is the TMAS (Taylor Manifest Anxiety Scale) scale. Hypothesis testing is done using the Paired Sample T-Test. Hypothesis testing shows a significance value of 0.000 (p <0.005) which indicates a significant difference in anxiety levels between pre-test and post-test. This means that Islamic self-efficacy training has a significant effect on reducing anxiety in facing the Qur’an memorization test of tahfidz students.